Saving in New Zealand: Measurement and Trends - Iris Claus; Grant Scobie (New Zealand Government, The Treasury, 2002)
This paper examines the trends in saving in New Zealand. It considers different sources of information about saving and highlights issues with the measurement of saving. Illustrations are provided of the impact of adjusting saving for both the effects of inflation and the inclusion of some items of expenditure, which are typically counted as consumption. The difficulty of drawing clear implications for policy on the basis of our existing knowledge and data on saving and wealth levels in New Zealand is highlighted. An appendix to the paper includes a comprehensive set of data on New Zealand saving and related variables.
Keywords: E21; C89; 330; Saving by sectors; measurement